Virtual Schools and Cyberpedagogy: the Hybrilog as a Bloniversity - Andrade, Pedro (PRISMA.COM, 2006)
This paper is structured as follows: 1. A brief conceptualization about virtual schools and digital learning, that aims to contribute to the emergence of a knowledge that speaks about schooling in a different way than traditional education theory does. This knowledge, regarding essentially digital schools, is cyberpedagogy. 2. We will present here a new type of blog, the hybrilog (Fig.1 and http://web.mac.com/pedro.andrade). An hybrilog is a blog consisting of several types of blogs, each one based on a different media (e.g. a text vlog, a video blog, etc.). The social sphere where blogs operate has been referred as blogosphere. Similarly, the social scape where hybrilogs circulate can be denominated hybridosphere. 3. A discussion concerning inedited kinds of learning spaces, namely the bloschool or bloniversity, which are, respectively, a digital school or a digital university that has the form and features of a blog. For instance, the hybrilog may act as a bloniversity, as we will see.